Impact of timing and method of virus inoculation on the severity of wheat streak mosaic disease - Wosula, Everlyne N.; McMechan, A.J.; Knoell, E.; Tatineni, S.; Wegulo, S.N.; Hein, G.L. (Scientific Societies, 2018)
Wheat streak mosaic virus (WSMV), transmitted by the wheat curl mite Aceria tosichella, frequently causes significant yield loss in winter wheat throughout the Great Plains of the United States. A field study was conducted in the 2013–14 and 2014–15 growing seasons to compare the impact of timing of WSMV inoculation (early fall, late fall, or early spring) and method of inoculation (mite or mechanical) on susceptibility of winter wheat cultivars Mace (resistant) and Overland (susceptible). Relative chlorophyll content, WSMV incidence, and yield components were determined. The greatest WSMV infection occurred for Overland, with the early fall inoculations resulting in the highest WSMV infection rate (up to 97%) and the greatest yield reductions relative to the control (up to 94%). In contrast, inoculation of Mace resulted in low WSMV incidence (1 to 28.3%). The findings from this study indicate that both method of inoculation and wheat cultivar influenced severity of wheat streak mosaic; however, timing of inoculation also had a dramatic influence on disease. In addition, mite inoculation provided much more consistent infection rates and is considered a more realistic method of inoculation to measure disease impact on wheat cultivars.